Seasonal Hydrography of Ameralik: A Southwest Greenland Fjord Impacted by a Land‐Terminating Glacier. Issue 12 (24th November 2021) - Stuart‐Lee, A. E.; Mortensen, J.; Kaaden, A.‐S. van der; Meire, L.
Abstract: Greenland's coastal zone encompasses a large number of fjords, many of which are impacted by glacial meltwater runoff from land‐terminating glaciers. This type of fjord has received limited research attention, yet may represent the future of other fjords currently impacted by marine‐terminating glaciers that are retreating. In this study we describe the seasonal hydrography of Ameralik, a fjord on the southwest coast of Greenland impacted by a land‐terminating glacier. To complement this analysis we compare our results with observations from the neighbouring Godthåbsfjord, which receives meltwater from both land‐ and marine‐terminating glaciers. We find that the absence of subglacial discharge and glacial ice in Ameralik has a strong impact on the inner fjord density profiles and on circulation. The mean temperature of the upper 50 m layer was lower in Ameralik than Godthåbsfjord in May, but by September was 2°C higher in Ameralik. Dense coastal inflows occur in the late winter months in Ameralik, flushing the fjord and contributing to the return to a weakly stratified state. During the runoff period the surface waters are subject to estuarine circulation and wind forcing, while at intermediate depths a density gradient between the inner and outer fjord regions produces an intermediate baroclinic circulation, resulting in the exchange of water in this layer and the deepening of isopycnals. During summer a large fraction of the meltwater runoff is retained within the fjord rather than being exported. A substantial export of this summer accumulated freshwater occurs in connection with coastal inflows during winter. Plain Language Summary: Marine‐terminating glaciers around Greenland are retreating, impacting the adjacent fjords with potential changes in the pathways taken by glacial meltwater. Few studies focus on fjords that receive meltwater only from land‐terminating glaciers, although knowledge of these systems can help us better understand how water from melting glaciers eventually ends up in the ocean in a future warmer climate. Here we present a full year of temperature and salinity observations from one such fjord on the southwest coast of Greenland and use these measurements to describe seasonal changes in water properties and circulation patterns. We compare the results with observations from a neighbouring fjord which receives meltwater from both land‐ and marine‐terminating glaciers. This comparison allows us to link differences observed between the fjords with the water movements associated with the type of glacier. While physical properties of the fjords, such as sill depth, play an important role in the circulation, the meltwater pathway also influences fjord hydrography, most prominently in the surface layers. This study will help us to understand the potential future state for many Greenland fjords with glaciers that are presently marine‐terminating. Key Points: We present seasonal hydrography from a fjord system (Ameralik) in southwest Greenland impacted by a land‐terminating glacier We compare our observations with the neighbouring Godthåbsfjord, which receives meltwater from both land‐ and marine‐terminating glaciers A large fraction of the seasonal freshwater input is retained in the fjord in summer and autumn, and is exported primarily in winter